Influence of urokinase continuous micro-pump on the malfunction of tunneled cuffed catheters in the hemodialysis patients - WANG Yan-jiang; XIE Xi-sheng; FENG Sheng-gang (Linchuang shenzangbing zazhi)
Objective To explore the influence of urokinase continuous micro-pump on the malfunction of tunneled cuffed catheters in the hemodialysis patients.Methods Thirty maintenance hemodialysis patients with the malfunction of tunneled cuffed catheters were chosen from the Hemodialysis Room of Nanchong Central Hospital.Patients were randomly divided into observation group(n=10),urokinase traditional sealed tube group(n=10)and urokinase continuous micro-pump into group(n=10).Blood flow velocity,dialysis adequacy and the occurrence of adverse catheter function within one month and complications were observed and compared among the groups.Results As compared with the observation group,the blood flow velocity of the dialysis and the dialysis adequacy in the urokinase traditional sealed tube group and the rokinase continuous micro-pump into group were significantly higher,and the occurrence frequency of adverse catheter function within one month was lower(P<0.05).Compared with the urokinase traditional sealed tube group,the blood flow velocity of the dialysis and the dialysis adequacy of the rokinase continuous micro-pump into group were higher,and the occurrence of adverse catheter function within one month was significantly lower(P<0.05).No bleeding complications occurred in all patients.Conclusions The dysfunction of the tunneled cuffed catheters can be significantly improved by the continuous micro pump of the urokinase.The effect of the continuous micro pump of the urokinase was significant,which was worthy of clinical application.